Pengaruh Kompetensi Guru Sekolah Minggu terhadap Pembentukan Karakter Anak-Anak Sekolah Minggu di Gereja Elim Kristen Indonesia (GEKI) MRC Marelan - Amce Sianturi; Herlina Sinaga; Marice Saragih; Joel Nababan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Character building of children is one of the main objectives of Sunday School ministry which is greatly influenced by teacher competence in implementing the learning process. Sunday School teachers are required to have pedagogical, personality, social, and professional competence in order to be able to instill Christian values ​​​​effectively to children. This study aims to analyze the influence of Sunday School teacher competence on the character building of children at the Elim Christian Church of Indonesia (GEKI) MRC Marelan. The study used a quantitative approach with a survey design and a positivistic paradigm. Data were collected by distributing questionnaires to respondents consisting of parents and children who actively attend Sunday School at GEKI MRC Marelan. Data were analyzed using descriptive and inferential statistics, including the Shapiro-Wilk normality test, correlation analysis, and coefficient of determination. The results showed that Sunday School teacher competence had a positive and significant effect on the formation of children's character with a correlation value (R) of 0.609 and a coefficient of determination (R²) of 0.370. These findings indicate that teacher competence contributes 37% to children's character formation, while the remaining 63% is influenced by factors outside the research model. This study concludes that improving Sunday School teacher competence through training, coaching, and professional development is a strategic step to increase the effectiveness of Christian education services and support the formation of children's character in accordance with biblical values.